A valuation-based test of market timing - Elliott, William B.; Koëter-Kant, Johanna; Warr, Richard S. (Journal of Corporate Finance, 2007)
We implement an earnings-based fundamental valuation model to test the impact of market timing on the firm's method of funding the financing deficit. We argue that our valuation metric provides a superior measure of equity misvaluation because it avoids multiple interpretation problems faced by the market-to-book ratio. It also eliminates the need to infer market timing based on the actions of corporate insiders or other indirect measures. We find a strong positive relation between the degree to which a firm is overvalued and the proportion of the firm's financing deficit that is funded with equity. This result is found cross-sectionally and through time and is robust to firm size, and other variables known to impact capital structure. We find evidence that overvaluation in the 1990s led to equity being increasingly preferred over debt. For a broad set of firms, market timing explains a significant portion of the variation in the type of security used to fund the financing deficit.